A Critical Appraisal of the Instrumented Indentation Technique and Profilometry‐Based Inverse Finite Element Method Indentation Plastometry for Obtaining Stress–Strain Curves. Issue 5 (16th February 2021) - Campbell, Jimmy E.; Zhang, Hannah; Burley, Max; Gee, Mark; Fry, Antony Thomas; Dean, James; Clyne, Trevor William
Abstract : A comparison is presented between conventional tensile stress‐strain curves and those obtained via two methodologies based on (spherical) indentation. The first, termed Instrumented Indentation Technique (IIT), involves conversion of load‐displacement data to stress‐strain curves via analytical expressions. This has been done using loads below 1 N ("nano") and in the kN range ("macro"). The other procedure, termed profilometry‐based indentation plastometry (PIP), is based on repeated finite element method (FEM) simulation, using the residual indent profile as the target outcome and obtaining the best fit set of parameter values in a constitutive stress‐strain law. This has been done on a macro scale only. The data from nano‐IIT tend to be very noisy and variable, whereas those from macro‐IIT are more reproducible and less noisy. With one of the two empirical formulations employed, the agreement of the macro‐IIT with experiment is close to being acceptable for the work hardening characteristics, although inferred values of the yield stress are in poor agreement with those from tensile testing. In contrast to this, the PIP procedure provides outcomes that are in close agreement with those from tensile testing, concerning both yield stress and work hardening. The causes of this are explored and discussed. Abstract : Comparisons are made, for three metals, between stress–strain curves obtained via two indentation‐based approaches. Instrumented Indentation Technique (IIT) (commonly done on a nanoscale) involves analytical conversion of load‐displacement data, whereas Profilometry‐based inverse finite element method (FEM) indentation plastometry (PIP) (usually coarser scale) involves iterative FEM, with residual indent profiles as target outcomes. The plots offer evidence that PIP is reliable, whereas IIT (particularly nano‐IIT) is not.